2006
DOI: 10.1021/ja056003z
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active Palladium Catalyst for Intermolecular Hydroamination. Factors that Control Reactivity and Additions of Functionalized Anilines to Dienes and Vinylarenes

Abstract: We report a catalyst for intermolecular hydroamination of vinylarenes that is substantially more active for this process than catalysts published previously. With this more reactive catalyst, we demonstrate that additions of amines to vinylarenes and dienes occur in the presence of potentially reactive functional groups, such as ketones with enolizable hydrogens, free alcohols, free carboxylic acids, free amides, nitriles, and esters. The catalyst for these reactions is generated from [Pd(eta(3)-allyl)Cl](2) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(189 citation statements)
references
References 57 publications
10
168
1
10
Order By: Relevance
“…This regioselectivity contrasts that obtained from reactions of arylamines, even with the same catalyst. [5] Consistent with the high activity of palladium-xantphos complexes as catalyst for the hydroamination of 1,3-dienes with arylamines, [5] the reaction of benzophenone hydrazone with isoprene occurred in the highest yields when catalyzed by the combination of [{Pd(allyl) Cl} 2 ] and xantphos. Nevertheless, this reaction catalyzed by palladium complexes of several other bisphosphines or generated from alternative precursors formed the hydroamination product in substantial yields.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…This regioselectivity contrasts that obtained from reactions of arylamines, even with the same catalyst. [5] Consistent with the high activity of palladium-xantphos complexes as catalyst for the hydroamination of 1,3-dienes with arylamines, [5] the reaction of benzophenone hydrazone with isoprene occurred in the highest yields when catalyzed by the combination of [{Pd(allyl) Cl} 2 ] and xantphos. Nevertheless, this reaction catalyzed by palladium complexes of several other bisphosphines or generated from alternative precursors formed the hydroamination product in substantial yields.…”
mentioning
confidence: 84%
“…[3,4] During studies to develop the scope of the hydroamination of dienes, [5][6][7] we found that the reactions of hydrazine and hydroxylamine derivatives occur irreversibly at the more substituted position of both prenyl and crotyl palladium intermediates. We explored this transformation further because, unlike the products from additions of aziridines, [3,4] the products from addition of hydrazine and hydroxylamine derivatives could be readily transformed into primary tert-alkylamines or sec-alkylamines.…”
Section: Abstract Allylic Substitution; Homogeneous Catalysis; Hydroamentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed mechanism [29] suggests that a ligand leaves the ruthenium center at the first stage. Subsequently, oxidative addition of an amine to coordinatively unsaturated ruthenium center takes place (Scheme 2).…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…(13)]. [71] Die Autoren gehen nicht von einem nucleophilen Angriff des Amins am Pt-koordinierten Olefin aus, sondern von einem Inner-Sphere-Mechanismus mit intramolekularer Insertion der C-C-Bindung in eine Pt-Amido-Bin- Vinylarene, deren Palladium-katalysierte Hydroaminierung ausführlich untersucht wurde, [65,72,73] Der Einsatz von ionischen Lösungsmitteln für chemische Reaktionen hat in den letzten Jahren bedeutend zugenommen. [78,79] Ionische Lösungsmittel zeichnen sich durch niedrige Flüchtigkeit aus, was umweltbezogene Vorteile mit sich bringen kann.…”
Section: Stickstoff-nucleophile: Platin-katalysierte Hydroaminierung unclassified